Association between fibrinogen/albumin ratio and arterial stiffness in patients with type 2 diabetes: A cross-sectional study - Chen, Chun-mei; Lu, Chun-feng; Liu, Wang-shu; Gong, Zhen-hua; Wang, Xue-qin; Xu, Feng; Ji, Jian-feng; Fang, Xing-xing (Frontiers in Pharmacology, 2023)
Background: Fibrinogen albumin ratio (FAR) is significantly correlated with the severity and prognosis of cardiovascular diseases (CVD). Arterial stiffness is an early lesion of CVD, but no studies have examined the correlation between arterial stiffness and FAR. This study aimed to examine the relationship between FAR and arterial stiffness in patients with type 2 diabetes (T2D), as measured by brachial-ankle pulse wave velocity (baPWV). Methods: In this cross-sectional investigation, patients with T2D were enrolled between January 2021 and April 2022. In each patient, the levels of fibrinogen, albumin, and baPWV in the serum were measured. A baPWV greater than 1800 cm/s was utilized to diagnose arterial stiffness. Results: The study included 413 T2D patients. The mean age of these participants was 52.56 ± 11.53 years, 60.8% of them were male, and 18.6% of them had arterial stiffness. There were significant differences in baPWV level and proportion of arterial stiffness (p < 0.001) between the four subgroups categorized by the FAR quartile. The relationships between the FAR and baPWV and arterial stiffness were significantly favorable in the overall population and subgroups of elderly men and non-elderly men (p < 0.01), while they were insignificant in subgroups of elderly and non-elderly women (p > 0.05). To investigate the correlation between the FAR and baPWV, the arterial stiffness, and the FAR in male T2D patients, respectively, multivariable logistic regression analysis and multiple linear regression analysis were developed. The lnFAR and lnbaPWV had a significant relationship in the multiple linear regression analysis fully adjusted model. After adjusting for potential covariables, multivariable logistic regression analysis revealed that the FAR has independently associated with arterial stiffness [OR (95% CI), 1.075 (1.031-1.120)]. In addition, receiver operating characteristic analysis indicated that the best FAR cutoff value for detecting arterial stiffness in male T2D patients was 76.67 mg/g. Conclusion: The level of FAR had an independent and positive correlation with baPWV and arterial stiffness in male patients with T2D, but not in female patients.